2013
DOI: 10.4037/ajcc2013692
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Capillary Blood Glucose Analysis in Patients Receiving Vasopressors

Abstract: Background Glycemic control in critically ill patients decreases infection and mortality. While capillary blood glucose values are accurate in normotensive patients and correlate with arterial samples, patients on vasopressors have altered peripheral perfusion that may affect accuracy of capillary blood glucose values tested using point of care devices. Objectives To compare capillary and arterial blood samples using point of care testing (POCT) with arterial blood samples using the clinical chemistry lab in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…To date, DTNI point of care studies have improved care processes for patient and family decision making at the end of life care (Johnson et al, 2010), improved patient safety and use of prevention strategies for patients undergoing alcohol withdrawal in the setting of acute myocardial infarction (Fullwood et al, in review), and improved the reliability of blood glucose testing and subsequent safety of intravenous insulin dosing after cardiothoracic surgery (Ellis et al, in review). In each case, new scientific discoveries reached patients in the form of an evidence‐based practice review, a new practice recommendation, or through partnered mentoring of clinicians to read new science more effectively.…”
mentioning
confidence: 99%
“…To date, DTNI point of care studies have improved care processes for patient and family decision making at the end of life care (Johnson et al, 2010), improved patient safety and use of prevention strategies for patients undergoing alcohol withdrawal in the setting of acute myocardial infarction (Fullwood et al, in review), and improved the reliability of blood glucose testing and subsequent safety of intravenous insulin dosing after cardiothoracic surgery (Ellis et al, in review). In each case, new scientific discoveries reached patients in the form of an evidence‐based practice review, a new practice recommendation, or through partnered mentoring of clinicians to read new science more effectively.…”
mentioning
confidence: 99%
“…A number of variables including hematocrit, PO 2 , PCO 2 , pH, and medications may interfere with or impact the accuracy of glucose meters 9,2931 . The accuracy of capillary (fingerstick) glucose measurement in critically ill patients is of even greater concern; as previous studies have demonstrated potentially dangerous discrepancies in capillary glucose measurement in patients on vasopressor therapy 10,17 , patients in shock 18 or with poor tissue perfusion 19 , and other critically ill patient populations 20 . Studies have also found that systematic (mean or median) glucose meter bias differs for capillary glucose meter samples compared to arterial or venous whole blood samples 10,27,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Though newer technologies may provide more accuracy 1214 , there is still concern about the use of meters in the critically ill 15,16 . Studies have demonstrated potentially dangerous discrepancies in capillary glucose measurement in patients on vasopressor therapy 10,17 , patients in shock 18 or with poor tissue perfusion 19 , and in other critically ill patient populations 20 . Consequently, no glucose meter is currently approved by the U.S. Food and Drug Administration (FDA) for use with capillary samples in critically ill hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, support in selecting appropriate system for specific patient has been issued recently (39). Several factors such as: edema, shock state, use of vasoconstrictors affect peripheral perfusion in ICU patients and disturb the accuracy of capillary glucose measurements (40,41). Moreover, glucose measurement in ICU is performed intermittently with the risk of undetected hypoglycemia, and the workload for the ICU nursing staff is considerable (42).…”
Section: Poc Continuous Glucose Monitoring Systems (Cgms) In Diabetesmentioning
confidence: 99%